EMOTION AND CONFLICT IN ALICE SEBOLD’S THE LOVELY BONES NOVEL - Fransisca, Candra; Natsir, M.; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research discussed emotion and conflict by Jack’s character in The Lovely Bones novel by Alice Sebold. The purposes of this study were to find the types of emotion experienced by Jack’s character and to find conflict caused by Jack’s emotion. This analysis includes to qualitative research method and a psychological approach. This research used The Lovely Bones novel as the source of data. The data derived from the dialogues and narration that represent emotion and conflict toward Jack’s character. The theories used in this analysis were the theory of emotion by Paul Ekman and the types of conflict by Lewis Coser. The result of this thesis showed that Jack as one of character in the novel shown various types of emotion. Those emotions are happiness, sadness, anger, fear, and surprise. In this case, that emotion caused conflict such as person versus self and person versus person that happened by Jack’s character in the novel.